Do physical activity and sedentary time mediate the association of the perceived environment with BMI? The IPEN adult study. (July 2020) - Van Dyck, Delfien; Cerin, Ester; Akram, Muhammad; Conway, Terry L.; Macfarlane, Duncan; Davey, Rachel; Sarmiento, Olga L.; Christiansen, Lars Breum; Reis, Rodrigo; Mitas, Josef; Aguinaga-Ontoso, Ines; Salvo, Deborah; et al.
Abstract: The study's main aim was to examine whether adults' accelerometer-based physical activity and sedentary time mediated the associations of neighbourhood physical environmental perceptions with body mass index (BMI) and weight status across 10 high- and middle-income countries. Data from the IPEN Adult study, an observational multi-country study (n = 5712) were used. Results showed that sedentary time was a non-significant or inconsistent mediator in all models. MVPA mediated the associations of street connectivity, land use mix-diversity, infrastructure/safety for walking and aesthetics with BMI in single models. In the multiple model, MVPA only fully mediated the relation between land use mix-diversity and BMI. This finding was replicated in the models with weight status as outcome. MVPA partially mediated associations of composite environmental variables with weight status. So, although MVPA mediated some associations, future comprehensive studies are needed to determine other mechanisms that could explain the relation between the physical environment and weight outcomes. Food intake, food accessibility and the home environment may be important variables to consider. Based on the consistency of results across study sites, global advocacy for policies supporting more walkable neighbourhoods should seek to optimize land-use-mix when designing and re-designing cities or towns. Highlights: MVPA mediated the relation between land use mix-diversity and BMI/weight status. Sedentary time was not a significant mediator in any of the models. All findings were similar in the 10 countries included in the study. Data from the IPEN study, a large-scale observational multi-country study were used.